Research on the Cultivation of College English Listening, Speaking, Reading, and Writing Ability by VR Technology. (12th August 2022) - Zeng, Zhen
Abstract : With the development of VR technology, it is possible to apply innovation to English teaching, and realize new breakthroughs and innovations in English teaching. In the background of information technology widely used in teaching, VR technology has become a very popular new technology because it can promote teaching better and make teaching effect more obvious; Through VR technology in English learning in listening, speaking, reading, and writing mode, we summarize the application of this technology in education industry at home and abroad, and put forward the purpose and significance of this research. Firstly, through the listening, speaking, reading, and writing mode of VR technology in English learning; In order to better evaluate the performance comparison under different modes, the score and weight distribution method are carried out for listening, speaking, reading, and writing. Secondly, by evaluating the value of E ( X ) in the nonexisting combination mode, the corresponding optimal proportion distribution scheme can be obtained. Finally, by comparing the scores of 8 groups of people under VR technology and statistical learning mode, the results show that VR technology has obvious advantages in improving listening, speaking, reading, and writing scores.